Measuring Goal Progress Using the Goal‐Based Outcome Measure in Youth Wellness Hubs Ontario—An Integrated Youth Services Network - Deb Chiodo; Aaron Turpin; Janis Wolfe; Karleigh Darnay; Jo Henderson (Health Expectations)
ABSTRACT Background Goal‐based outcomes (GBOs) are a tool for youth‐directed care and have been successfully used in a small number of community youth mental health settings. Youth Wellness Hubs Ontario (YWHO) uses GBO data provided by youth to deliver care that amplifies youth voice in decision‐making about supports that are important and meaningful to them. Objective This article summarizes GBO data from youth receiving clinical and nonclinical services at YWHO hubs to develop a more nuanced understanding of the type of goals set by young people when accessing services. Design A quantitative design utilizing content analysis was adopted to organize goal data into descriptive categories, which were further analysed by goal distribution and mean rating scores. Participants Youth (n = 1851) from 22 YWHO networks provided GBO and demographic data. Data were collected across 7348 service visits and youth provided 19,290 goals. Consent for service was obtained, which included the use of personal health information to monitor progress, quality improvement and for evaluation purposes. Variables GBO data included a written goal and scaled goal rating component. Service visits and demographic variables were tabulated, whereas a mean score for goal achievement (i.e., goal rating) was generated. Results Six themes emerged from the analysis, including improve mental health (42.7% coverage, mean rating 3.9), connect to services (20.9% coverage, mean rating 4.4), intrapersonal development (15.3% coverage, mean rating 3.1), interpersonal development (12.0% coverage, mean rating 3.5), improve physical health (5.4% coverage, mean rating 2.9) and address substance use/other addiction (3.0% coverage, mean rating 3.1). Conclusion The GBO tool allows youth to actively participate in setting their own assessment and outcome criteria, indicate which areas they require support and wish to improve and personalize shared decision‐making. Patient or Public Contribution The YWHO model was co‐developed by youth, families, service providers and researchers. Youth and families informed the data measures and collection processes described within this article.